A New Four‐Component L*‐Dependent Model for Radial Diffusion Based on Solar Wind and Magnetospheric Drivers of ULF Waves - Kyle R. Murphy; Jasmine Sandhu; I. Jonathan Rae; Thomas Daggitt; Sarah Glauert; Richard B. Horne; Clare E. J. Watt; Sarah Bentley; Adam Kellerman; Louis Ozeke; Alexa J. Halford; Sheng Tian; et al. (Space Weather)
Abstract Waves which couple to energetic electrons are particularly important in space weather, as they drive rapid changes in the topology and intensity of Earth's outer radiation belt during geomagnetic storms. This includes Ultra Low Frequency (ULF) waves that interact with electrons via radial diffusion which can lead to electron dropouts via outward transport and rapid electron acceleration via inward transport. In radiation belt simulations, the strength of this interaction is specified by ULF wave radial diffusion coefficients. In this paper we detail the development of new models of electric and magnetic radial diffusion coefficients derived from in‐situ observations of the azimuthal electric field and compressional magnetic field. The new models use L∗ as it accounts for adiabatic changes due to the dynamic magnetic field coupled with an optimized set of four components of solar wind and geomagnetic activity, Bz, V, Pdyn, and Sym−H, as independent variables (inputs). These independent variables are known drivers of ULF waves and offer the ability to calculate diffusion coefficients at a higher cadence then existing models based on Kp. We investigate the performance of the new models by characterizing the model residuals as a function of each independent variable and by comparing to existing radial diffusion models during a quiet geomagnetic period and through a geomagnetic storm. We find that the models developed here perform well under varying levels of activity and have a larger slope or steeper gradient as a function of L∗ as compared to existing models (higher diffusion at higher L∗ values).